Features and prospects of the Russian civil aircraft industry development under sanctions pressure from Western countries - V. V. Lapushkin (Вестник университета)
The specifics and prospects of development of the Russian civil aircraft industry under sanctions pressure from Western countries have been considered. The study analyzes secondary data from open sources. The main provisions and conclusions of the work are as follows. The United States of America and its European satellites have imposed comprehensive sanctions against Russian air carriers, including a ban on aircraft deliveries. Lessors who owned foreign airplanes made demands for their return, and foreign registrars suspended airworthiness certificates for domestic airplanes. Western sanctions against Russian airlines have caused significant damage to Russia, but have also become a serious stimulus for the domestic aviation industry development. Significant time and investment will be required to resolve the problems encountered. Russia has the necessary potential to restore the aviation industry and ensure safe passenger and cargo transportation in the required volume. The country is currently working systematically to revitalize the industry, implementing advanced developments and establishing serial production of a wide range of civil aircraft. The success of the domestic aviation industry development depends mainly on the state’s efforts, as it has the access to almost all production and design capacities. In addition, effective measures are needed to influence the air transportation industry in order to balance the supply and demand for aircraft.